Re: Causes of Hospital Readmissions after Urologic Cancer Surgery - Özgür Yaycıoğlu (Journal of Urological Surgery)
Unplanned readmissions after surgery are a cause for anxiety and inconvenience for the patient and financial burden for the healthcare system. It has been advocated that unplanned readmission rates can be used as a metric for quality of patient care. In the light of the changes in health care policy with an emphasis on reducing readmissions, Schmid and coworkers used the American College of Surgeons National Surgical Quality Improvement Program database to examine the causes and predictors of readmissions after urologic oncology surgical procedures, namely radical prostatectomy (RP), radical nephrectomy (RN), partial nephrectomy (PN), and radical cystectomy (RC). The overall unplanned 30-day readmission rate was 5.5%. Approximately two thirds of readmissions occurred within the first 10 days following hospital discharge. Comparing with the other procedures, RC patients experienced the highest rate (15.9%) for readmissions. For RP and PN, minimally invasive approach was associated with decreased odds for readmissions. Better analyzing the causes and developing strategies to prevent early readmissions after urologic cancer surgery would undoubtedly help to improve patient outcomes and decrease the health care costs.